RADIONUCLIDE SCANNING WITH I-123 IN GRAVES DISEASE - Putu Diah Vedayanti; Lisna Astuti; Elisanti Dwi Martadiani (E-Jurnal Medika Udayana, 2014)
Graves’ disease is the most common form of thyrotoxicosis which caused byautoimmune that attacks the thyroid gland. This disease will lead such followingsyndromes: thyrotoxicosis, goiter, ophthalmopathy, dermopathy. The sensitive TSHassay is the single best screening test for hyperthyroidism, and in most outpatientclinical situations. But when there is a doubt to distinguish diffuse toxic goiter (Graves’disease) from autonomous toxic nodule (Plummer’s disease), radioinuclide scanning canbe performed. I-123 is one of the preferable radiosisotope because it can produce clearimage and short enough half-life, although the price is expensive.